DEALING WITH ANCESTORS: ARCHEOLOGICAL RESEARCH IN RUPAC, HUARAL. - van Dalen Luna, Pieter (2015)
The results of archaeological research carried out in the archaeological complex of Rupac, the most monumental site in the Lima region, but until now one of the most unknown is presented. Rupac has a continuous occupation in the late pre-Hispanic period, defined by the development of culture in its independent Atavillos stage (Late Intermediate) and under the rule of Tawantinsuyu (Late Horizon). Rupac dominates the Kullpi, funeral mausoleums buildings by way of a tripartite organization, within which and around conducting activities in honor of the ancestors type architecture.